Pengaruh Lingkungan Belajar Abad 21, Kompetensi Digital , dan Motivasi Belajar terhadap Prestasi Belajar Siswa SMKN 1 Bogor - Rakha Wahyuanda; Marsofiyati Marsofiyati; Achmad Fauzi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to examine the impact of 21st-century learning environment, digital competence, and learning motivation on student academic achievement at SMK Negeri 1 Bogor. Education plays a crucial role in shaping academic performance, especially in the face of the challenges of the digital era, where students are required to possess skills that are relevant to the needs of the 21st century. Therefore, it is essential to investigate how factors such as learning environment, digital competence, and learning motivation influence students' academic performance. This study uses a quantitative approach with a survey method and Structural Equation Modeling Partial Least Squares (SEM-PLS) data analysis technique. The population in this study consists of all students in grades X and XI in the Office Management and Business Services program at SMK Negeri 1 Bogor, totaling 281 students. A selected sample of 167 students was chosen using proportionate sampling based on the Slovin formula. The independent variables in this study include the 21st-century learning environment, digital competence, and learning motivation. The 21st-century learning environment consists of the family, school, and community environments, which play an important role in creating a conducive learning atmosphere. Digital competence refers to students' ability to use technology for learning, communication, and assessment. Meanwhile, learning motivation includes both internal and external factors that encourage students to achieve optimal learning outcomes. The results of the analysis show that all three variables—21st-century learning environment, digital competence, and learning motivation—have a positive and significant effect on students' academic achievement. This indicates that improvements in these three variables can contribute to enhancing students' academic performance at SMK Negeri 1 Bogor, ultimately helping them succeed in the globalized world.